Design and implementation of an agent-based Web service composition framework - Marquez-Rangel, Oscar (University of Ottawa (Canada), 2004)
This thesis proposes the design of a Web service composition framework in which individual Web services are represented by software agents that collaborate to create composite services. The design includes the language to define composite services, the protocol that software agents follow when executing composite services and the architecture of the proposed framework. The proposed architecture provides: (i) the incorporation of standard technologies for service discovery into a dynamic service-discovery process; (ii) high levels of scalability and flexibility without requiring the service provider to host additional modules; and (iii) the incorporation of composite services that are successfully executed even when negligible individual services fail. The proposed framework was evaluated with different sets of users that simultaneously requested the same composite service. An improvement to the basic architecture was made to decrease the processing times when the number of users is increased. (Abstract shortened by UMI.)
Keywords: Computer Science.